The Eksistence of Kitab Kuning Use in Learning: A Study at Salafiyah Tarbiyah Islamiyah Boarding School of Padang Indonesia - Ibrahim, Anas Malik; Wiza, Rahmi (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2021)
The kitab kuningÂ has an important role in the oldest Islamic education institution in Indonesia, namely Islamic boarding schools. Even today, the kitab kuning still exists and it is used by students and becomes the benchmark for a boarding school. This study aims to determine the kitab kuning learning method applied in the Salafiyah Tarbiyah Islamiyah boarding school of Padang Indonesia. This study uses a qualitative method with a case study approach. Data sources were taken from twelve informants consisting of student representatives, teachers, and students using purposive techniques. The research data was taken through in-depth interviews with all informants. The results of this study indicate that there are three methods of learning the kitab kuningÂ used by the Salafiyah Tarbiyah Islamiyah Islamic boarding school of Padang Indonesia. The three methods are the halaqqoh method, the talaqqi method, and the memorization method.